Model Pendidikan Iman Anak Dalam Keluarga Berbasis Anjuran Apostolik Familiaris Consortio Dalam Menumbuhkan Perilaku Altruistik - Wea, Donatus; Wolomasi, Agustinus Kia (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2022)
The purpose of this research is to find out the actual model of children's faith education in the family in the Salib Suci Gudang Arang parish, to study and analyze it as a reference to produce a new model. The model that is suitable for children's faith education for the growth of altruistic behavior is the one based on the Familiaris Consortio of Pope John Paul II. Primary data were obtained through observation and interviews with 30 informants consisting of parents, children, the family commission of the Archdiocese of Merauke, the parish family section and senior families who are examples (role models). The findings are that parents do not play their main role in educating children's faith because they do not know the pattern and do not get the assistance that is their right as a provision to educate children's faith. For that we need a model that can help them in educating children's faith. The finding in this model is the involvement and responsibility of Church authorities in planning, implementing, monitoring and evaluating through the relevant commissions or sections. In this way, Catholic families will be able to carry out their roles well as first and foremost educators for children's faith so that their altruistic behavior grows which is resulted in sincere sharing, solidarity and self-sacrifice.